Comparative analysis of post‐transplant lymphoproliferative disorder after kidney transplantation versus hematopoietic stem cell transplantation. (10th May 2014) - Yoon, Jae‐Ho; Lee, Seok; Kim, Hee‐Je; Lee, Jong‐Wook; Min, Woo‐Sung; Chung, Byung Ha; Yang, Chul Woo; Kim, Yong‐Soo; Kim, Ji‐Il; Moon, In Sung; Oh, Eun Ji; Park, Gyeong‐Sin; et al.
Summary Post‐transplant lymphoproliferative disorder (PTLD) is a major complication caused by immune‐suppression after transplantation. Survival outcome is known to be poor and the characteristics are not fully understood because of its rare incidence. This single center retrospective study enrolled 41 adult PTLD patients after kidney‐transplantation (KT, n = 28) and hematopoietic stem cell transplantation (HSCT, n = 13) from 1992 to 2012. We compared the characteristics and estimated the survival outcomes according to several factors [age‐adjusted‐IPI (aaIPI), pathologic subtype, viral status, extranodal manifestation] and added some significant parameters to aaIPI scoring system. Post‐HSCT‐PTLD patients were younger and showed earlier onset, and viral status was more frequently identified. Ten‐year OS of the entire group was 44% but the 10‐year OS was not significantly different between post‐KT‐PTLD and post‐HSCT‐PTLD (39% vs. 56%, P = 0.860). The time onset of PTLD and viral statuses were not meaningful, however, aaIPI, age > 50, extranodal manifestation and monomorphic subtype were predictive for OS. We used those factors for PTLD‐specific scoring which showed intermediate‐risk (HR = 7.1, P = 0.019) and high‐risk (HR = 16.5, P = 0.001) presented worse OS compared to low‐risk subgroup. Although the treatment strategies were heterogenous, this study showed comprehensive PTLD data between KT versus HSCT, and our PTLD‐specific scoring might be validated by another larger studies.